2023
DOI: 10.18502/fid.v19i40.11901
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Fibroblast Cell Viability Following Treatment with Different Concentrations of Green Tea, Aloe Vera and a Mixture of their Extracts

Abstract: Objectives: Various studies have identified green tea and Aloe vera as a suitable medium for avulsed teeth. The aim of this study was to evaluate and compare the viability of periodontal ligament (PDL) fibroblasts following treatment with the extracts of these two plants and their mixture. Materials and Methods: Human PDL fibroblasts were purchased and treated with different concentrations of Aloe vera, green tea, and a combination of these two extracts. Hank’s balanced salt solution and culture medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Transplant of GMSCs inhibited the loss of alveolar bone induced by periodontitis and enhanced formation of new alveolar bone. Moreover, previous studies have reported that the conditioned medium of periodontal ligament-derived mesenchymal stem cells (PDLSCs) enhanced periodontal tissue regeneration, but isolating PDLSCs is difficult and requires multiple periodontal membranes from extracted teeth [ 232 , 233 ]. To provide an alternative to PDLSCs, a study investigated whether the conditioned medium from GMSCs (GMSC-CM) exhibited an effect similar to that of the conditioned medium of periodontal ligament-derived mesenchymal stem cells [ 234 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transplant of GMSCs inhibited the loss of alveolar bone induced by periodontitis and enhanced formation of new alveolar bone. Moreover, previous studies have reported that the conditioned medium of periodontal ligament-derived mesenchymal stem cells (PDLSCs) enhanced periodontal tissue regeneration, but isolating PDLSCs is difficult and requires multiple periodontal membranes from extracted teeth [ 232 , 233 ]. To provide an alternative to PDLSCs, a study investigated whether the conditioned medium from GMSCs (GMSC-CM) exhibited an effect similar to that of the conditioned medium of periodontal ligament-derived mesenchymal stem cells [ 234 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Studying fibroblast responses to Tideglusib may give light on the drug's potential impacts on dentin-pulp complex regeneration and periodontal tissue health. 27 Furthermore, the use of fibroblasts in this study aligns with the goal of assessing Tideglusib biocompatibility and possible functions in promoting or inhibiting tissue regeneration in the oral environment.…”
Section: Discussionmentioning
confidence: 97%
“…7 The content of green tea, namely flavonoids, plays an important role in the healing process such as antiinflammatory and increasing the number of fibroblasts. 8 Natural ingredients derived from shrimp shells, namely chitosan, in the wound healing process can stimulate tissue regeneration, activate inflammatory cells such as fibroblasts, and remodeling process during the wound healing process. 9 In vivo research conducted by Qin et al, chitosan provides a non-protein matrix during tissue growth, assists in natural clotting, and blocks nerve endings to reduce pain.…”
Section: Introductionmentioning
confidence: 99%